A8.16 The Role of Adipocytokines in Osteoarthritis Osteophyte Formation. (25th February 2013) - Junker, S; Krumbholz, G; Frommer, KW; Rehart, S; Lange, U; Steinmeyer, J; Rickert, M; Schett, G; Müller-Ladner, U; Neumann, E
Abstract : Background and Objectives: Although obesity is an established risk factor in osteoarthritis (OA), there is limited information about the role of adipose tissue derived factors in bone formation. Adipocytokines such as adiponectin, resistin, and visfatin, are known to be associated with the pathogenesis of rheumatoid arthritis (RA) and OA. Adipocytokines are locally produced in RA and OA joints by osteoblasts, osteoclasts, and chondrocytes. In contrast to their joint-destructive effects in RA, the role of adipocytokines in OA bone remodelling and osteophyte formation is unclear. Therefore, the adipocytokine expression during osteophyte development and in cells of bone formation was analysed as well as their effect on these cells. Methods: Osteophytes, cartilage, and osteoblasts were obtained from OA patients during joint replacement surgery. Serial sections of bone tissue were stained (Masson trichrome, TRAP) and scored from grade one (no ossification, mainly connective tissue and cartilage) to five (ossified mineralised osteophytes, <10% connective tissue, ossified remodelling zones). Immunohistochemistry against alkaline phosphatase, collagen-type II, adiponectin, resistin, and visfatin was performed. OA osteoblasts were stimulated with adiponectin or resistin and immunoassays for IL-6, IL-8, and MCP-1 were performed. Results: All adipocytokines were detectable in cultured osteoblasts and all osteophyte grades. In non ossified osteophytes (grade 1), especially adiponectin and to a lower extent resistin and visfatin were detectable in connective tissue fibroblasts. In ossified osteophytes (grade 2–5), resistin and visfatin and to a lower extend adiponectin were expressed by osteoblasts and resistin and visfatin by osteoclasts. In all osteophyte grades adiponectin was detectable in blood vessels and visfatin was found in about 50% of the chondrocytes. Osteoblast stimulation with adiponectin increased the release of the inflammatory mediators IL-6 (2.6-fold), IL-8 (4.9-fold), and MCP-1 (2.1-fold). In contrast, resistin led to a non-significant decrease of these factors. The osteoblast populations showed individual differences in the baseline expression of the analysed factors and in their responsiveness to adipocytokines. Conclusions: The adiponectin and visfatin expression in osteophyte connective tissue and cartilage suggests their involvement in early osteophyte development. Resistin and visfatin in osteoblasts and osteoclasts in ossified osteophytes indicates a role in osteophyte formation at later stages. The stimulation of osteoblasts with adiponectin induces the release of inflammatory mediators. Therefore, the analysed adipocytokines most likely are involved in osteophyte formation at different stages and correspondingly affect cells of cartilage and bone formation to a different extent. Funded by the ANCYLOSS project of the German Ministry of Research and Education (BMBF).